2020
DOI: 10.1136/jim-2019-001195
|View full text |Cite
|
Sign up to set email alerts
|

Platelets and Platelet Extracellular Vesicles in Hemostasis and Sepsis

Abstract: Platelets, cell fragments traditionally thought of as important only for hemostasis, substantially and dynamically contribute to the immune system’s response to infection. In addition, there is increasing evidence that externally active platelet entities, including platelet granules and platelet extracellular vesicles (PEVs), play a role not only in hemostasis, but also in inflammatory actions previously ascribed to platelets themselves. Given the functions of platelets and PEVs during inflammation and infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 122 publications
0
97
0
Order By: Relevance
“…We inferred that platelet activation played an important role in the progression of SP. Platelets are activated after exposure to platelet agonists, which are released from already activated platelets, impaired cells, or other inflammatory factors [20]. After activation, platelets take part in the immune system via various fashions, including direct interaction with pathogens, regulation of inflammatory responses by the congenital and complement immune system, and contact with leukocytes and specific immune system [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We inferred that platelet activation played an important role in the progression of SP. Platelets are activated after exposure to platelet agonists, which are released from already activated platelets, impaired cells, or other inflammatory factors [20]. After activation, platelets take part in the immune system via various fashions, including direct interaction with pathogens, regulation of inflammatory responses by the congenital and complement immune system, and contact with leukocytes and specific immune system [20].…”
Section: Discussionmentioning
confidence: 99%
“…Larger platelet expresses more procoagulant surface proteins and intracellular thromboxane A2 (TXA2), presenting a greater prothrombotic potency. TXA2 can also activate the pulmonary vascular endothelium, known to be integral in the process of acute lung injury related to serious infection [20]. In addition, platelet size has been reported to be a predictive marker of cardiovascular events [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most known non-cellular effects are linked to platelet-derived EVs. Many studies show that platelet EVs promote coagulation and thus play an important role in the maintenance of homeostasis [ 41 ]. Their pro-coagulant activity is linked to the PS exposure on the EVs that can provide a catalytic surface for assembly of the coagulation complexes [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although an earlier work showed that virulent isolates produced high titers of hemolysin, were resistant to inactivation by serum complement (68), further information is needed to uncover the mechanism of VVHmediated evasion of complement killing, which may help us to better understand the basis of the V. vulnificus infection process in human blood. Being at the crossroads between the immune system, clotting cascade, and endothelial cells, platelets seem to be an appealing central mediator and possible therapeutic target for sepsis (69)(70)(71). The mechanism of bacterial-induced platelet activation by pore-forming toxins has been well characterized in other Gram-positive bacteria (72).…”
Section: The Role Of the Vvh In Disease And Pathogenesismentioning
confidence: 99%